Corporate Secretarial Bilingual Activity: An English Teaching Proposal Based on Corpora Directed to the Secretaries - Lourenço, José Roberto (The ESPecialist, 2015)
This article presents part of research conducted in the field of Corpus Linguistics about the use of corpora in English Language Teaching specifically directed to corporate secretarial activities. The study developed at the doctoral level had FATEC-SP students as voluntary respondents to a questionnaire on corporate secretarial activities; the responses presented as one of the most important and frequent secretarial activities, "Reading, Preparation and Presentation of Administrative Report". We present a model of practice in English Teaching with an initial focus on "Company History, Strategies and Structure".